Cruising through uncertainty: cell phones and the politics of display and disguise in Inhambane, Mozambique - Archambault, J (John Wiley & Sons Inc., 2013)
Cell phones play a conspicuous role in the way young people in Inhambane, Mozambique, juggle visibility and invisibility in their everyday lives. By opening up new social spaces within which individuals can engage in various pursuits with some degree of discretion, cell phone communication helps redress socioeconomic inequalities while preserving an unpleasant public secret about the workings of Mozambique’s postwar economy: that young women are encouraged to exchange sexual favors for material gain. Drawing on the literature on secrecy and building on the local notion of “visão,” I propose an extended use of the idea of “social navigation” that captures concerns about appearances and the reproduction of wider epistemologies of ignorance.